2020
DOI: 10.3390/nu12010223
|View full text |Cite
|
Sign up to set email alerts
|

Could Omega 3 Fatty Acids Preserve Muscle Health in Rheumatoid Arthritis?

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by a high prevalence of death due to cardiometabolic diseases. As observed during the aging process, several comorbidities, such as cardiovascular disorders (CVD), insulin resistance, metabolic syndrome and sarcopenia, are frequently associated to RA. These abnormalities could be closely linked to alterations in lipid metabolism. Indeed, RA patients exhibit a lipid paradox, defined by reduced levels of total, low-density lipoprotein (LDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 141 publications
(203 reference statements)
0
8
0
1
Order By: Relevance
“…Serum levels of n-3 PUFA parallel dietary fish consumption 25 , 26 and correlate with a 27% reduction in all-cause mortality risk of elderly 27 . Marine-derived n-3 PUFAs also have anti-inflammatory effects on RA progression 28 . In prospective, double-blind, randomized controlled studies by Kremer et al 29 , 30 , dietary supplementation of n-3 PUFAs dose-dependently decreases RA activity parameters (tender joint count, swollen joint count and duration of morning stiffness) and serum levels of IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of n-3 PUFA parallel dietary fish consumption 25 , 26 and correlate with a 27% reduction in all-cause mortality risk of elderly 27 . Marine-derived n-3 PUFAs also have anti-inflammatory effects on RA progression 28 . In prospective, double-blind, randomized controlled studies by Kremer et al 29 , 30 , dietary supplementation of n-3 PUFAs dose-dependently decreases RA activity parameters (tender joint count, swollen joint count and duration of morning stiffness) and serum levels of IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…RA patients have an increased risk for developing insulin resistance, which is influenced by RF seropositivity, higher disease activity, prednisone use, and visceral and thigh intermuscular adiposity [ 24 , 28 ]. The increased accumulation of toxic lipid mediators and consequent lipotoxicity in skeletal muscles may also stimulate mitochondrial dysfunction, that, together with insulin resistance, contribute to cardiovascular disorders and sarcopenia [ 29 ]. Insulin resistance, cardiovascular disorders, and sarcopenia, associated with an increased intramuscular fat compared to healthy subjects, are frequently associated with RA [ 30 ].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Grip strength significantly improved following a diet high in PUFAs and supplemented with fish oil providing 1.6 g EPA and 1.1 g DHA per day for 4 weeks (116 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) to 136 (12-88) mmHg); (p < 001) [43]. Similarly, in Kavanagh et al's study, a 4-week elemental diet followed by reintroduction of food significantly improved grip strength (140.2 ± 96 to 155.9 ± 98.3 mmHg) (p = 0.008) [36].…”
Section: Grip Strengthmentioning
confidence: 99%
“…Omega-3 PUFAs regulate signaling pathways of anti-oxidants and alter inflammatory pathways by competing with omega-6 PUFAs which are transformed to pro-inflammatory eicosanoids [18]. Omega-3 PUFAs are the most studied supplements in RA with several clinical trials conducted among adults over the years [19,20]. A recently published systematic review [21] concluded that supplementation with omega-3 PUFAs led to substantial improvements in the duration of early morning stiffness (EMS), pain levels, erythrocyte sedimentation rate (ESR), physical function, grip strength, joint tenderness and levels of leukotriene B4 (LTB4).…”
Section: Introductionmentioning
confidence: 99%